Pengaruh Ukuran Perusahaan, Umur Perusahaan, Likuiditas, dan Leverage terhadap Audit Report Lag (Studi pada Perusahaan Consumer Goods Terdaftar di BEI Tahun 2019-2020) - Andrew Christian Sudjono; Amelia Setiawan (Owner : Riset dan Jurnal Akuntansi, 2022)
Financial statements contain useful information for many users. The usefulness of financial statements affects how the users need to analyze financial statements timely for the decision-making process. To maintain the accuracy and transparency of financial statements, each company must request an audit service from an audit firm, which requires a long time. This may lead to the phenomenon known as audit report lag. In concern of the timeliness of financial statement reporting, this research wanted to find a solution that can be taken by regulators and companies so that financial statements can be reported timely. The purpose of this research is to analyze the impact of firm size, firm age, liquidity, and leverage on audit report lag. This research is quantitative, using the simple random sampling technique. The samples used for this research are the consumer goods sector companies that are listed in BEI from 2019 until 2020, with a total of 72 samples used. The data is analyzed using SPSS 24 for the classic assumption test, descriptive statistical analysis, and multiple linear regression test. The results showed that firm size affects negatively the audit report lag, firm age also affects negatively toward the audit report lag, liquidity affects negatively audit report lag and leverage also affects the audit report lag negatively. The results also showed that firm size, firm age, liquidity, and leverage affect the audit report lag simultaneously. The implication of this research may help companies and regulators in supporting the timeliness of financial statement reporting.